Features of Using the Russian Version of the Dispositional Mindfulness Scale (CAMM) for Teenagers - Zotova L.E; Gubanov A.V; Sidyacheva N.V (Moscow State University of Psychology and Education, 2020)
This study aims to adapt the Child and Adolescent Mindfulness Measure - CAMM (Greco, Baer, Smith) scale for a Russian-language sample of adolescents. Modern domestic and foreign studies of dispositional mindfulness demonstrate its connection with the psychological health of young people. In this context, the diagnosis of dispositional mindfulness can be used for predictive purposes to identify the level of psychological well-being, social adaptation, and behavioral problems of adolescents. However, no diagnostic tools have been provided that are aimed at this age group. For psychometric verification of the Russian version of the dispositional mindfulness scale, the factor structure of the original and adapted version of the scale was compared, confirmation factor analysis, Spearman-Brown and Cronbach coefficients were used, criteria validity was evaluated, and a centile scale and a scale of questionnaire responses were developed. The study involved 411 teenagers (52% of girls and 48% of boys) living in Moscow and the Moscow region. The age range is from 13 to 15 years. The adapted scale is characterized by a satisfactory degree of internal consistency, which is confirmed by the value of the Spearman-Brown and Cronbach coefficients. In contrast to the one-factor original version of the scale, confirmation analysis of the Russian version revealed a two-factor structure with overlapping factors. Adolescent dispositional mindfulness is positively correlated with relevant constructs such as psychological well-being and negatively correlated with internalized and externalized adolescent problems. There was a positive reliable correlation with the readiness of adolescents to help and a negative one - with aggression in the classroom. The conducted research suggests that the adapted Russian-language scale of dispositional mindfulness has demonstrated good psychometric indicators and this tool can be considered as suitable for practical use.